Comparison of different types of outlet frits in slurry‐packed capillary columns. Issue 17 (21st July 2014) - Franc, Martin; Sobotníková, Jana; Coufal, Pavel; Bosáková, Zuzana
<x xml:space="preserve">Abstract</x> Fused‐silica capillary columns for high‐performance liquid chromatography with 320 and 250 μm inner diameter were prepared by slurry packing with 5 and 3 μm Nucleosil C18 stationary phase. Different types of mechanical and monolithic outlet frits were used and their influence on the resulting column performance was evaluated. Columns with quartz wool exhibited symmetrical peaks and low theoretical plate height, and the preparation time was short. The performance of monolithic frits varied based on type of monolith, length of the frit, and silanization procedure. The best frit performed similarly to the quartz wool ones, but the preparation took several hours. Their main advantage lies in the possibility of on‐column detection, because the detection window can be burnt immediately behind the frit.